Level of Running Speed in SSB Andeskal Football Athletes Kandang Lemonade Age 13-15 Bengkulu City - Dwingki Marta Putra (Penerbit Jurnal Indonesia, 2022)
The background of this research is the lack of running speed skills in SSB Andeskal Athletes at Lemonade Cage aged 13-15 years in Bengkulu City. The design of this research is descriptive research, while the method used in this research is the method of observation and measurement sheets. The population of this study were SSB Andeskal Kandang Limun athletes with a total sample of 25 athletes using total sampling technique. The variable of this study was the running speed of Andeskal SSB athletes at the Lemonade Cage aged 13-15 years in Bengkulu City. Data was collected using a 50 meter running test according to (Apri Agus, 2017: 171), and the data analysis technique used was descriptive statistical techniques with frequencies and percentages through categorization. Based on the results of the research and analysis of the data carried out, it was found that the running speed of the Andeskal SSB athletes at the Lemonade Cage aged 13-15 years in Bengkulu City, there were 12 athletes or 48% who were classified as good categories, 6 athletes or 24% who were classified as medium categories, 7 athletes or 28% belonging to the moderate category. Based on the results of this study it can be concluded that the running speed of Andeskal SSB athletes at the age of 13-15 years in Bengkulu City is in the good category